Numerical Investigation of Hydraulic Fracture Propagation in Naturally Fractured Reservoirs Based on Lattice Spring Model - Kaikai Zhao; Pengfei Jiang; Yanjun Feng; Xiaodong Sun; Lixing Cheng; Jianwei Zheng (Geofluids)
Hydraulic fracturing has been extensively employed for permeability enhancement in low-permeability reservoirs. The geometry of the hydraulic fracture network (HFN) may have implications for the optimization of hydraulic fracturing operations. Various parameters, including the in situ stress, treatment parameters (injection rate and fluid viscosity), and orientation of natural fractures (NFs), can significantly affect the interactions between hydraulic fracture (HF) and NFs and the final HFN. In this study, a lattice-spring code was employed to determine the impact of various parameters on the geometry of the HFN. The modelling results indicated that with a large stress difference, the global orientation of the fracture propagation was restricted to the direction of maximum principal stress, and the number of fracture branches was reduced. The geometry of the HFN changed from circular to elliptical. In contrast, with an increase in the fluid viscosity/injection rate, the evolution of the geometry of the HFN exhibited the opposite trend. The global orientation of HF propagation tended to remain parallel to the direction of maximum principal stress, regardless of the branching and tortuosity of the fracture. The variations in the ratio of tensile fracture (HF) to shear fracture (shear slip on NF) can be significant, depending on the stress state, treatment parameters, and preexisting NF network, which determine the dominant stimulation mechanism. This study provides insight into the HF propagation in naturally fractured reservoirs.